EMERGENCY REPORTING SYSTEM (ERS) UNTUK KASUS KRIMINALITAS PADA POLRESTABES KOTA MAKASSAR - Rahmaniar, Rahmaniar; Arda, Abdul Latief; Yuyun, Yuyun (Universitas Teknokrat Indonesia, 2024)
This study aims to implement Google Maps API technology and the Havershine algorithm in the Emergency Reporting System (ERS) application at the Polrestabes Makassar, where this system runs on Android with quick access for user using the buttons on the screen and the volume up button. System development in this application uses the waterfall method with the UML (Unified Modeling Language) design language. Meanwhile, software using JAVA, PHP, HTML, CSS, Java script and MySql is used for database management. Data collection was obtained through observation, interviews and literature study. Based on the results of testing by 18 respondents consisting of 12 members of the public or reporters and 6 officers, it was found that the average percentage of respondents' scores for questionnaire questions was 82.5% with a Cronbach's Alpha value of 0.73. It can be concluded that the emergency reporting system application is considered very reliable. Testing this application using a button on the application screen ran smoothly on the first try with the average time the victim pressed the button to record less than 1 second or 0.64 seconds and the time it took for a message to reach the helper or police officer was 11.66 seconds. Testing the emergency notification application using the volume up (+) button on the device completed smoothly in 1.55 trials with the average time between the victim pressing the volume button and recording being 5.00 seconds and the time until the rescue team arrived was 14.00 seconds. This time includes the time required to set the maximum volume and activate the device screen. The percentage of correspondence between the accurate location points of the reporter and the recipient of the report using the Google Maps API with the Havershine algorithm to determine the relevant police station based on the closest distance is approximately 75% accurate on average with a distance difference of approximately 45.5 meters.